Gestures & animation on the iPad. - Pilone, Dan; McLaughlin, Brett (O'Reilly breakdown., 2010)
The iPad brings a new level of user interactivity to mobile apps. If your app can't deal with touches, swipes, and pinches, you're not going to see great interest and sales. In this O'Reilly Breakdown, Dan Pilone gives you hands-on experience using the iPad GestureRecognizer API. You'll also build animations to give the user instant feedback when they interact with your application. The experts in the O'Reilly Breakdown live video series not only break down the concepts of difficult and complex subjects, they also demonstrate practical implementation and use. Each episode features an experienced programmer, developer, or software designer working on real-world challenges, ranging from iPad user interface design and multi-tasking on Android phones to caching in cloud-based applications.